2012
DOI: 10.4103/0974-7761.115143
|View full text |Cite
|
Sign up to set email alerts
|

Bullying perceptions among post-graduate dental students of Andhra Pradesh, India

Abstract: Introduction: of bullying are common in field of medicine. However, the extent of this problem remains unknown. Bullying among students and professionals has been studied in developed countries, but has received limited, practically, no attention in India. This study was thus planned with an aim to know the prevalence and the perceptions of bullying by the post-graduate dental college students of Andhra Pradesh, India. Objectives: This study aimed to find out bullying practices experienced by the students and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The reported prevalence of sexual harassment of medical students by patients ranges from 12% to 71% 3 . However, there is little research on the prevalence of harassment of dental students, and most existing research focuses only on sexual harassment by patients or on harassment from fellow students and instructors 11,12 . One Brazilian study reported that 9% of dental students had experienced sexual harassment by a patient or a patient's relative 8 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported prevalence of sexual harassment of medical students by patients ranges from 12% to 71% 3 . However, there is little research on the prevalence of harassment of dental students, and most existing research focuses only on sexual harassment by patients or on harassment from fellow students and instructors 11,12 . One Brazilian study reported that 9% of dental students had experienced sexual harassment by a patient or a patient's relative 8 .…”
Section: Introductionmentioning
confidence: 99%
“…One Brazilian study reported that 9% of dental students had experienced sexual harassment by a patient or a patient's relative 8 . Research in a dental school in India found no harassment of students by patients 11 . However, given that rates of harassment by patients reported by dental professionals are similar to those of other health professions, 13 it is likely that the prevalence of harassment of students by patients is higher than the existing literature suggests.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sources influencing emotional labour included both clients, such as patients and their family members, and members of their own professional organizations, including supervisors and peers 18 . However, research on workplace violence experienced by dental hygienists in dental clinics is scarce, while research on similar violence experienced by dentists 19 and dental college students 20 is comparatively more abundant.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, no action was taken following the workplace incident, and no workplace policies appeared to be in place to manage such incidents (Garvin and Sledge 1992;Binmadi and Alblowi 2019). International research on workplace violence among health care practitioners in various fields shows similar results, with factors such as the age, sex, occupation, and work hours of the health care practitioner and the characteristics of the health care institution and system being independent determinants of experiencing workplace violence (Lahari et al 2012;Abdellah and Salama 2017;Pinar et al 2017;Norton et al 2017). Workload pressures, occupational stress, and organizational culture are also known to be contributing factors to workplace violence (Sanders and Turcotte 2010;Carter et al 2013;Berthelsen et al 2017).…”
Section: Introductionmentioning
confidence: 99%